Changing perspectives of literacy, identity and motivation: implication for language education - Mercieca, Paul (Springer, 2014)
This chapter affirms the value of secure but flexible cultural identities in developing a form of critical intercultural literacy which is not merely as a set of skills, but a deeper set of understandings. Drawing on the findings of a study of a migrant group in Australia, it suggests that such literacy can be acquired in third spaces between the familiar and the new. From a sociocultural perspective, it is argued that for successful language learning and social interaction, the development of critical intercultural literacy should overarch the narrower concepts of communicative competence and cultural literacy. It is also argued that teaching and learning are much less effective if educator and learner cultural values conflict, and if school literacy learning does not connect with personal experience.